Silent Ozu three crime dramas = Sono yo no tsuma - Brand, Neil 1958-; Schisgall, Oscar 1901-1984 (The Criterion collection, 2015)
"In noirish darkness, a man commits a shocking robbery. But, as we soon learn, this seeming criminal mastermind is actually a sensitive everyman driven to desperation by the need to provide for his family. Unfolding over the course of one night, Yasujiro Ozu’s That Night’s Wife combines suspense with the emotional domestic drama one associates with the filmmaker’s later masterpieces, and employs beautifully evocative camera work." [criterion.de]